Assessing how biofilms modulate stream periphyton metacommunity assemblage: A translocation experiment - Daniel Zamorano; Travis Ingram; Fabio A. Labra; Christoph D. Matthaei (Ecology, 2025)
The role of three‐dimensional structural complexity in shaping communities has been increasingly studied, and evidence indicates that vertical stratification favors coexistence through niche partitioning. Despite the clear relationship between three‐dimensional structure and community assemblages, its role in shaping metacommunity processes is still unclear. To address this knowledge gap, we carried out a translocation experiment using stream periphyton (benthic microalgae) as a model community. Structural complexity in stream periphyton is observed when thicker biofilms develop, reducing hydraulic stress and improving nutrient uptake, particularly for understory taxa. In this experiment, we exposed ceramic tiles in a source river for 4, 11, or 21 days, creating a biofilm biomass and successional gradient. We then translocated these tiles to 10 receiving rivers in two phosphorus enrichment categories (low, high). After 25 days, we collected all tiles and evaluated biofilm biomass and the periphyton community. We determined community similarity post‐translocation using the Bray–Curtis distance, comparing translocated tiles to pre‐translocation communities and to control tiles from the receiving rivers. Translocated tiles remained more similar to their pre‐translocation community when the source and receiving rivers were more similar to each other and when pre‐colonization time was longer (11 or 21 days), whereas biofilm biomass was not a key predictor. Further, translocated tiles became more similar to their receiving river communities when pre‐colonization time was shorter (4 days) and when receiving river biofilm biomass was higher, suggesting that neighborhood biofilm biomass could indicate local propagule pressure. Low‐phosphorus sites exhibited lower biofilm biomass and high proportions of taxa from both receiving rivers and the source river on translocated tiles, which indicated a more important role of species sorting. By contrast, high‐phosphorus sites displayed greater neighborhood biomass and translocated tiles less similar to receiving rivers or the source river due to a higher proportion of rare taxa, which suggested mass effects. This experiment expands our knowledge of the role of three‐dimensional community structure in driving metacommunity processes by considering environmental contexts, biomass as a proxy of structural complexity, and successional time.

Ecological role of marine mammals in the Magellan Strait: Insights from trophic modeling - Daniela Haro; Fabio A. Labra; Sergio Neira; Juan Carlos Hernández-Padilla; Francisco Arreguín-Sánchez (Ecological Modelling, 2025)

Acidification and high-temperature impacts on energetics and shell production of the edible clam Ameghinomya antiqua - Sebastián I. Martel; Carolina Fernández; Nelson A. Lagos; Fabio A. Labra; Cristián Duarte; Juan F. Vivanco; Claudio García-Herrera; Marco A. Lardies (Frontiers in Marine Science, 2022)
Warming and ocean acidification are currently critical global change drivers for marine ecosystems due to their complex and irreversible effects on the ecology and evolution of marine communities. Changes in the chemistry and the temperature of the ocean impact the biological performance of marine resources by affecting their energy budget and thus imposing energetic restrictions and trade-offs on their survival, growth, and reproduction. In this study, we evaluated the interplaying effects of increased p CO 2 levels and temperature on the economically relevant clam Ameghinomya antiqua , an infaunal bivalve inhabiting a wide distributional range along the coast of Chile. Juvenile clams collected from southern Chile were exposed to a 90-day experimental set-up emulating the current and a future scenario projeced to the end of the current century for both high p CO 2 /low-pH and temperature (10 and 15°C) projected for the Chilean coast. Clams showed physiological plasticity to different projected environmental scenarios without mortality. In addition, our results showed that the specimens under low-pH conditions were not able to meet the energetic requirements when increased temperature imposed high maintenance costs, consequently showing metabolic depression. Indeed, although the calcification rate was negative in the high- p CO 2 scenario, it was the temperature that determined the amount of shell loss. These results indicate that the studied clam can face environmental changes for short-term periods modifying energetic allocation on maintenance and growth processes, but with possible long-term population costs, endangering the sustainability of an important benthic artisanal fisheries resource.

The Importance of Intraspecific Variation for Niche Differentiation and Species Distribution Models: The Ecologically Diverse Frog Pleurodema thaul as Study Case - Aura M. Barria; Daniel Zamorano; Andrés Parada; Fabio A. Labra; Sergio A. Estay; Leonardo D. Bacigalupe (Evolutionary Biology, 2020)

Assessing how body size affects the species-time relationship in a shallow marine benthic megafauna community exposed to a strong hypoxia disturbance - Fabio A. Labra; Eduardo Hernández-Miranda; Renato A. Quiñones (Marine Biology, 2020)

Resilience of an aquatic macrophyte to an anthropogenically induced environmental stressor in a Ramsar wetland of southern Chile - Eduardo Jaramillo; Cristian Duarte; Fabio A. Labra; Nelson A. Lagos; Bruno Peruzzo; Ricardo Silva; Carlos Velasquez; Mario Manzano; Daniel Melnick (Ambio, 2019)

The relative role of ecological interactions and environmental variables on the population dynamics of marine benthic polychaetes - Fabio A. Labra; Rodrigo A. Moreno; Sergio A. Alvarado; Franklin D. Carrasco; Sergio A. Estay; Marcelo M. Rivadeneira (Marine Biodiversity, 2018)

Dispersal and transient dynamics in metapopulations - Fabio A. Labra; Nelson A. Lagos; Pablo A. Marquet (Ecology Letters, 2003)
Recent studies of spatially explicit metapopulation models have shown the existence of complex transient behaviour (supertransients and mesotransients) characterized by spontaneous changes in the system's dynamics after thousands or hundreds of generations, respectively. Their detection in simple ecological models has been taken as evidence that transient dynamics may be common in nature. In this study, we explore the generality of these phenomena in a simple one‐dimensional spatially explicit metapopulation model. We investigate how frequently supertransient behaviour emerges in relation to the shape and type of the dispersal kernel used (normal and Laplace), system size, boundary conditions and how sensitive they are to initial conditions. Our results show that supertransients are rare, are heavily affected by initial conditions and occur for a small set of dispersal parameter values, which vary according to kernel type, system size, and boundary conditions. Similarly, mesotransients emerge over a very narrow range of dispersal parameter values and are rare under all circumstances. Thus, transient dynamics are not likely to be either common or widespread in simple models of ecological systems.